2019
DOI: 10.1038/s41598-019-45976-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum and plasma brain-derived neurotrophic factor and influence of storage time and centrifugation strategy

Abstract: The aims of the study were to clarify the impact of storage time and centrifugation strategy on brain-derived neurotrophic factor (BDNF) levels in human serum and plasma samples. In addition, we analyzed associations between BDNF levels, cardiorespiratory fitness and waist circumference. Seventeen healthy males (25.2 (4.1) years) were included in the study. Blood samples were drawn after an overnight fast and treated to different protocols, varying in time before centrifugation and centrifugation strategy. BDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 37 publications
(51 reference statements)
1
101
3
Order By: Relevance
“…Thus, the method used to measure the circulating neurotrophin can introduce bias from one study to another. Serum preparations that allow clotting and BDNF release from platelets retrieve a much higher amount of BDNF, in comparison with measurements of BDNF from blood samples containing anti-coagulants [115].…”
Section: Brain Plasticity Adult Neurogenesis and Physical Activitymentioning
confidence: 99%
“…Thus, the method used to measure the circulating neurotrophin can introduce bias from one study to another. Serum preparations that allow clotting and BDNF release from platelets retrieve a much higher amount of BDNF, in comparison with measurements of BDNF from blood samples containing anti-coagulants [115].…”
Section: Brain Plasticity Adult Neurogenesis and Physical Activitymentioning
confidence: 99%
“…However, circulating BDNF is largely attributable to platelet precursor cells, megakaryocytes, which synthesize BDNF under the platelet BDNF promoter 23 . It is not clear whether circulating BDNF measured in blood reflects brain BDNF levels 24 . Despite the importance of BDNF on brain functions and increasing interest in Val66Met on psychiatric/cognitive symptoms, studies on the effects of Val66Met on cancer-related fatigue are non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…While under the old concept that posit that the brain was isolated, central measures were relevant, studies have demonstrated that BDNF cross the blood-brain barrier in both directions [6,41]. Studies demonstrating that peripheral and central BDNF levels are associated are further providing support to our approach [42].…”
mentioning
confidence: 80%